Nutritional Behaviour of Rural and Urban Over Weight and Obese Women - Karpugam V., Sarada D. (Drugs and Cell Therapies in Hematology, 2021)
Ethnic and traditional food habits are being replaced by westernised fast foods, soft drinks and increased meat consumption. Westernization of diets has increased the energy density and this is particularly a problem for the poor in all countries who are at risk of both obesity and micronutrient deficiencies. In addition, a sharp decline in cost of vegetable oils and sugar means that they are now in direct competition with cereals as the cheapest food ingredients in the world. This has caused a reduction in the proportion of the diet that is derived from grain and grain products and has greatly increased world average energy consumption, although this increase is not distributed evenly throughout the world’s population (Drewnowski, 2000). A significant difference (p = 0.473*) was found at 0.05 level, indicating that the women varied in their Dietary Diversity Score (DDS).